(untitled) (Development Service Industry Management, 2024)
The article discusses the results of the conducted research on the relevance of introducing engineering and graphic technology for designing hotel and restaurant business establishments. The undoubted advantages of engineering graphics in visualization capabilities and time-saving in the process of planning, organizing, adjustment and operation of hotels and restaurants, ensuring their stable and sustainable operation due to the created safety system are proved. The results of the conducted research clearly demonstrate the significant role and importance of engineering graphics tools in the formation of high-quality projects of the hotel and restaurant business, a package of documents for licensing, certification and other materials required by the current legislation necessary for opening a hotel and restaurant business and its further operation. The role and importance of engineering graphics in ensuring the safety of hotel and restaurant buildings is multifaceted and extremely important. It helps to expand the possibilities of effective design, maintenance and modernization of constructions and engineering systems, which in turn guarantees the safe operation of the building throughout its entire life cycle. The use of modern graphic tools allows to solve complex technical tasks, minimizing risks and increasing the level of safety and comfort for building users. The conducted research made it possible to determine the capabilities of engineering graphics in analyzing the safety of building constructions; to study the impact of graphic models on decision-making on the safety of buildings operation; to reflect the capabilities of engineering graphics in designing evacuation routes for guests and staff in case of emergency; to characterize the importance of engineering graphics technology in the process of locating fire protection systems and equipment; to provide a description of the possibilities of visualization of electrical, plumbing, ventilation and other systems to ensure the safe operation of establishments; to determine the importance of using engineering graphics for maintenance and modernization of electrical, plumbing, ventilation and other systems to ensure the safe operation of facilities.